Legal Protection for Creditors in Credit Agreements with Mortgage Guarantees - B, Sumiyati; Tamrin, Muh; Gumanti, Vidya (JIHAD : Jurnal Ilmu Hukum dan Administrasi, 2024)
The main problem in the research is how legal protection is for creditors in credit agreements with collateral. The research method used is normative legal research, which is conceptualized in a statutory regulation, and examined in relation to protection for creditors in credit agreements with collateral for mortgage rights. The results of the research show that legal protection for creditors is that they are given the right to take repayment of debts to previous creditors in the form of executing the object of collateral rights using method (1). Parate execution (direct execution), namely the creditor holding the first mortgage right has the right to sell the object of the mortgage right under his own authority through a public auction. (2). Execution with the assistance of a judge is a request for execution by the creditor to the Chairman of the District Court to carry out the execution with a judge's decision which has definite and binding legal force. (3). Execution of sales under the hand, namely an agreement between the giver and the holder of the mortgage right to carry out a sale under the hand of the object of the mortgage right to obtain the highest possible price that is useful for all parties.